2021
DOI: 10.3390/foods10123150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nitrite, Ethyl Carbamate, and Biogenic Amines in Four Types of Fermented Vegetables

Abstract: Nitrite, ethyl carbamate, and biogenic amines in fermented vegetables are considered harmful compounds. In this study, the concentration of the nitrite, ethyl carbamate, and biogenic amines in four different varieties of fermented vegetables in China was determined. The results show that the nitrite concentration in the fermented cabbage was the highest, followed by fermented mustard, fermented bamboo, and fermented radish. Additionally, nitrite concentration in two fermented cabbage samples and one fermented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Reducing the nitrite content of fermented vegetables during storage may be achievable by changing the type of packaging; accumulation of nitrite in fermented cabbage was reduced by vacuum packaging and the nitrite content at the end of storage was 56.04% and 36.31% lower than that of aerobic packaging and NaCl solution packaging, respectively (Zhao et al ., 2021). The concentrations of nitrites and bioamines during the fermentation of bamboo, cabbage and mustard should be closely monitored and controlled (Yu et al ., 2021).…”
Section: Microorganisms In Fermented Vegetablesmentioning
confidence: 99%
“…Reducing the nitrite content of fermented vegetables during storage may be achievable by changing the type of packaging; accumulation of nitrite in fermented cabbage was reduced by vacuum packaging and the nitrite content at the end of storage was 56.04% and 36.31% lower than that of aerobic packaging and NaCl solution packaging, respectively (Zhao et al ., 2021). The concentrations of nitrites and bioamines during the fermentation of bamboo, cabbage and mustard should be closely monitored and controlled (Yu et al ., 2021).…”
Section: Microorganisms In Fermented Vegetablesmentioning
confidence: 99%
“…The traditional fermentation process involves several steps [21]. Firstly, fresh vegetables are selected and washed.…”
Section: The Fermentation Process Of Traditional Fermented Vegetablesmentioning
confidence: 99%
“…The amount of nitrite in various pickles differs based on the ingredients used. According to recent studies, the maximum nitrite level has been found in fermented cabbage, followed by fermented mustard, bamboo, and radishes [ 122 ]. The concentration of nitrite is related to the composition of the microbial community of the pickles.…”
Section: Safety Problems In Fermented Vegetables and Current Solutionsmentioning
confidence: 99%